Pengaruh Kepercayaan pada Pemerintah, Literasi Pajak, dan Digitalisasi Pajak terhadap Kepatuhan Wajib Pajak - Aida Nur Aini; Erna Chotidjah Suhatmi; Ety Meikhati (ITB AAS INDONESIA, 2025)
This research seek to analyze the impact of Trust in Government, Tax Literacy, and Tax Digitalization on Tax Compliance. The study focuses on individual taxpayers registered at the Surakarta Primary Tax Office (KPP Pratama Surakarta), involving a total sample of 100 respondents. A quantitave method was applied, utilizing primary data obtained trough questioneres distributed both face-to-face and online via via G-Forms through WhatsApp. Data processing and analysis were carried out using SPSS version 26. Based on the analysis, the R² value obtained 0.307, indicating that 30.7% of the variation in Tax Compliance can be accounted for by the independent variables used in the model. The F-test results yield a significance level of 0.000, suggesting that the variables examined collectively exert a statistically significant influence on Tax Compliance. The partial test (t-test) shows that Trust in Government (Sig. 0,051) has a significance value greater than 0.05, meaning it does not significantly influence Tax Compliance. Meanwhile, Tax Literacy (sig. 0.000) and Tax Digitalization (sig. 0.007) significantly influence Tax Compliance, as indicated by significance values below 0.05.